Antimicrobial evaluation of Punica granatum peel and aril dry extract - Oliveira, Evaldo Hipólito de (2020)
Medicinal plants have been used by men in the treatment of diseases since ancient times. Brazil is a country with great biological and cultural diversity that keeps the consumption of herbal medicines as popular practice and there is a growing worldwide interest in plant-derived products. Punica granatum, popularly known as pomegranate, is widely distributed in Brazil and according to studies, it presents a good anti-inflammatory and antimicrobial potential due to the presence of phenolic compounds (tannins, terpenoids among others) in their composition. For this reason, the present study aimed to evaluate the in vitro antimicrobial potential of the dry extract of the peel of fruits of P. granatum by drilling technique in agar against bacterial strains of Staphylococcus aureus and Escherichia coli and the fungus Candida albicans. The inoculation wells of P. granatum extracts produced considerable inhibition halos, especially in higher concentrations (5, 2.5, 1.25 and 0.62 mg). Bacterial and also fungal antibiotic activity was demonstrated. This performance of the plant was already expected taking into account the various studies published on the matter. We concluded that P. granatum can be used in the production of new antibacterial phytotherapics.